Nanopatterned adhesive, stretchable hydrogel to control ligand spacing and regulate cell spreading and migration - Deng, Jie; Spatz, Joachim P.; Wei, Qiang (ACS nano, 2017)
Spatial molecular patterning enables the regulation of adhesion receptor clustering and can thus play a pivotal role in multiple biological activities such as cell adhesion, viability, proliferation, and differentiation. A wide range of nanopatterned, adhesive interfaces have been designed to decipher the essence of molecular-scale interactions between cells and the adhesive interface. Although an interligand spacing of less than 70 nm is a proven prerequisite for the formation of stable focal adhesions, there is a paucity of data concerning how cells behave on substrates featuring heterogeneous adhesiveness. In this study, a stretchable hydrogel functionalized with a quasi-hexagonally arranged nanoarray was stretched along one direction, resulting in ligands periodically arranged in a pattern resembling a centered rectangular lattice with an interligand spacing smaller than 70 nm in one direction and greater than 70 nm in the orthogonal direction. This substrate was utilized to modulate interligand spacing and investigate cell adhesion and migration. An interligand spacing larger than 70 nm—even in just one direction—prevented the establishment of stable focal adhesions. The stretched interface promoted dynamic remodeling at cell contacts, resulting in higher cellular mobility. Our nanopatterned stretchable hydrogel permits reversible control over cell adhesion and migration on nanopatterned ligand interfaces.